(3TQM Gdabg GdCcHQs - (3GdSjfhHj, EdjGS Hf EHQGgje, J (B891 (3g`s ((3JHQjRj RGOg MSjf Hf EHQGgje GdOjhQjcjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj NUU faQG ef YHGOg djJabghG aj GdCehQ GdOjfjIs
(3BNQgG (B:s
(3YUefG Gddg ef GdRjZ hGdQO hLYdfG ef GdeSJeScjf HMHd GdgOGjI hGdJbi hGdMeO ddg Ydi GdJeGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 8s
(3gOjI GdYGQajf (B1 / 225s
(3cTa GdXfhf (B2 / 1287s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJhMjO hGdedd hGdfMds